Consumption modelling considering different socio-economic household types - Thomas Drosdowski; Britta Stöver; Marc Ingo Wolter (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2015)
Private households constitute one of the main economic sectors. The underlying house-hold structure determines income and consumption aggregates. For example, changes in the population composition induced by demographic change or shifts in the income structure through redistributional policy measures affect the level and the structure of the purchased goods and services. Socio-economic information should hence be consid-ered when modelling private consumption demand. This contribution aims to integrate more advanced socio-economic structures in a macroeconomic model environment. The socio-economic consumption module includes detailed information on consumption purposes and income components from the German Household Budget Survey. The module interacts with the macro-econometric input-output model INFORGE through a feedback mechanism. A consistent link between micro-based survey data and macroeco-nomic information based on the System of National Accounts is possible. Thus, macroeco-nomic effects of social characteristics are taken into account.
Keywords: C8; E2; 330; socio-economic modelling; household types by size and social status; household consumption; income structure; Privater Konsum; Privater Haushalt; Deutschland